Focused deterrence strategies and crime control an updated systematic review and meta‐analysis of the empirical evidence - Braga, Anthony Allan (Criminology & public policy, 2018)
Focused deterrence strategies are increasingly being applied to prevent and control gang and group‐involved violence, overt drug markets, and individual repeat offenders. Our updated examination of the effects of focused deterrence strategies on crime followed the systematic review protocols and conventions of the Campbell Collaboration. Twenty‐four quasi‐experimental evaluations were identified in this systematic review. The results of our meta‐analysis demonstrate that focused deterrence strategies are associated with an overall statistically significant, moderate crime reduction effect. Nevertheless, program effect sizes varied by program type and were smaller for evaluations with more rigorous research designs.